Fatigue design of steel and composite structures. Eurocode 3, Eurocode 4, - Nussbaumer, Alain, 1964- (ECCS Eurocode design manuals., 2011)
This volume addresses the specific subject of fatigue, a subject not familiar to many engineers, but still relevant for proper and good design of numerous steel structures. It explains all issues related to the subject: Basis of fatigue design, reliability and various verification formats, determination of stresses and stress ranges, fatigue strength, application range and limitations. It contains detailed examples of application of the concepts, computation methods and verifications.